A brief history of stereoscopy. (5th June 2013) - King, R. Duane
Abstract : We focus on a timeline for stereoscopic visualization. The timeline can be conceived as three distinct eras. The first era was characterized by the full understanding of stereoscopic vision and the development of the stereoscope technology for viewing three dimensional images. The first era was greatly enabled by the simultaneous development of photographic technologies. The second era was characterized by the development of polarized light and anaglyph stereo technology and was mainly manifested with a dramatic outpouring of motion pictures. The third era, the digital era, was developed in connection with virtual reality and scientific data visualization. WIREs Comput Stat 2013, 5:334–340. doi: 10.1002/wics.1264 This article is categorized under: Statistical and Graphical Methods of Data Analysis > Statistical Graphics and Visualization Statistical and Graphical Methods of Data Analysis > Virtual Reality